Achieving Error-free posts in Asynchronous facilitation: Findings from the Discussion Forum Posts of 100 Level Students of National Open University of Nigeria - Ugoala, Bibian (West African Journal of Open and Flexible Learning, 2023)
In order to achieve error-free posts in asynchronous discussion forum in online teaching among students of Open Distance e-learning (ODeL), this study examines patterns of errors in the use of the simple past tense on the discussion forum posts of the 2018/2019 academic session of one hundred level students of National Open University of Nigeria. Past tense errors occur when the wrong verb tense is used in writing. Using Corder’s, quoted in Ellis (1994), steps in error analysis, and classification, the study found that of the three hundred and forty- eight (348) students who responded to the post, one hundred and ninety-three students (55.5%) committed errors of omission. Nineteen students (5.5%) added redundant morphemes to irregular verbs. One hundred and thirty-six students (39%) mis-selected the wrong morphemes in marking simple past tense. The findings from the study suggest that the reason for the errors are attributed to the inconsistencies in the English language especially with past tense formation in irregular verbs. The study recommends that in ODeL, leaners in a second language situation be given more online lectures that weaves in past tense usage in English language; this will enable them to have a good grasp of the rules guiding simple past tense formation in English, and ensure correctness in the use of the right verbs by students in their posts. The study concludes that students’ verb usage in online posts can be improved if online teaching platforms build in prompts that immediately pops up the correct verb whenever a student makes use of the wrong verb in posts. This will be an innovation that will encourage motivation to learn and could culminate to decline in leaners’ dropout rate in ODeL in Nigeria. Résumé: Afin de réaliser des messages sans erreur dans le forum de discussion asynchrone dans l'enseignement en ligne parmi les étudiants de l'apprentissage en ligne à distance ouverte (ODeL), cette étude examine les modèles d'erreurs dans l'utilisation du passé sur les messages du forum de discussion de la session académique 2018/2019 des étudiants de niveau cent de l'Université nationale ouverte du Nigéria. Les erreurs de temps passé se produisent lorsque le mauvais temps de verbe est utilisé dans l'écriture. En utilisant les étapes de Corder, citées dans Ellis (1994), dans l'analyse et la classification des erreurs, l'étude a révélé que sur les trois cent quarante-huit (348) étudiants qui ont répondu au message, cent quatre-vingt-treize étudiants (55,5%) ont commis des erreurs d'omission. Dix-neuf élèves (5,5 %) ont ajouté des morphèmes redondants aux verbes irréguliers. Cent trente-six étudiants (39%) ont mal sélectionné les mauvais morphèmes en marquant le passé simple. Les résultats de l'étude suggèrent que la raison de ces erreurs est attribuée aux incohérences de la langue anglaise, en particulier en ce qui concerne la formation du passé dans les verbes irréguliers. L'étude recommande que, dans le cadre de l'enseignement ouvert et à distance, les apprenants en situation de langue seconde reçoivent davantage de cours en ligne qui intègrent l'utilisation du passé en anglais ; cela leur permettra de bien comprendre les règles qui régissent la formation du passé simple en anglais et d'assurer l'utilisation correcte des bons verbes par les étudiants dans leurs cours. L'étude conclut que l'utilisation des verbes par les étudiants dans les messages en ligne peut être améliorée si les plateformes d'enseignement en ligne intègrent des invites qui font immédiatement apparaître le verbe correct chaque fois qu'un étudiant utilise un verbe erroné dans ses messages. Cette innovation encouragera la motivation à apprendre et pourrait aboutir à une baisse du taux d'abandon des apprenants dans l'ODel au Nigéria. Mots-clés : Analyse des erreurs, passé simple, ODeL, poste en ligne asynchrone, Université nationale ouverte du Nigeria (NOUN).